Forced Exception Handling: You can never discount the human element in programming. - Neville-Neil, George V. (Communications of the ACM, 2017)
The article discusses forced exception handling in relation to distributed systems and catastrophic failures. Topics include notes left in error-handling components of software code, the opinions of programmers about error-handling sections of code, and the fixing of exceptions in relation to other aspects of programming.